2014
DOI: 10.1021/ac500317c
|View full text |Cite
|
Sign up to set email alerts
|

Objective Set of Criteria for Optimization of Sample Preparation Procedures for Ultra-High Throughput Untargeted Blood Plasma Lipid Profiling by Ultra Performance Liquid Chromatography–Mass Spectrometry

Abstract: Exploratory or untargeted ultra performance liquid chromatography-mass spectrometry (UPLC-MS) profiling offers an overview of the complex lipid species diversity present in blood plasma. Here, we evaluate and compare eight sample preparation protocols for optimized blood plasma lipid extraction and measurement by UPLC-MS lipid profiling, including four protein precipitation methods (i.e., methanol, acetonitrile, isopropanol, and isopropanol-acetonitrile) and four liquid-liquid extractions (i.e., methanol combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
185
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(198 citation statements)
references
References 50 publications
5
185
0
Order By: Relevance
“…41 High recoveries of BAs associated with high reproducibility were found in urine respectively around 92.7% and 8.58%. Recovery of the standards in plasma and serum were around 4% less than for urine recoveries, whereas reproducibility around 2% higher than for urine.…”
Section: Bile Acid Recoveries In Human Serum Plasma and Urinementioning
confidence: 91%
See 1 more Smart Citation
“…41 High recoveries of BAs associated with high reproducibility were found in urine respectively around 92.7% and 8.58%. Recovery of the standards in plasma and serum were around 4% less than for urine recoveries, whereas reproducibility around 2% higher than for urine.…”
Section: Bile Acid Recoveries In Human Serum Plasma and Urinementioning
confidence: 91%
“…Supernatant (100 µL) was transferred to 0.5 mL Eppendorf 96-deepwell plates and 300 µL of ice-cold methanol were added to each sample. 41 All plates were heat sealed (Thermo Fisher 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Mass spectrometry parameters were as follows: capillary voltage was set at 1.5 kV, cone voltage at 60 V, source temperature 150 °C, desolvation temperature at 600 °C, desolvation gas flow at 1000 L/h, cone gas flow at 150 L/h. Bile acid species yielding characteristic fragments when subjected to collision-induced dissociation were assayed using multiple reaction monitoring (MRM), while those that did not fragment were assayed by selected ion monitoring (SIM).…”
mentioning
confidence: 99%
“…To solve these issues most researchers utilize sample preparation combined with chromatographic separation to decrease the complexity of the sample and remove substances that have a negative impact on the MS detection. A plentitude of publications have suggested various protocols for unbiased and simple sample preparation for global metabolite profiling of blood-, urine-or cell-based samples (Bruce et al 2009;Dunn et al 2011;León et al 2013;Michopoulos et al 2009;Pereira et al 2010;Rico et al 2014;Sarafian et al 2014;Tulipani et al 2013;Want et al 2010;Vorkas et al 2015;Vuckovic 2012). However, any selection of a particular approach will come with its own benefits and drawbacks in relation to the composition of the sample.…”
Section: Sampling and Sample Preparationmentioning
confidence: 99%
“…A particular focus during the last ten years has been on improving metabolite coverage (Vuckovic 2012), though little emphasis has been placed on the suitability of these protocols in regards to data quality (Sarafian et al 2014;Tulipani et al 2013Tulipani et al , 2015. The relationship between metabolite coverage and consistent reliable data is a complicated matter since these factors depend on each other.…”
Section: Sampling and Sample Preparationmentioning
confidence: 99%
“…For large-scale studies, the sample preparation method should be as simple and robust as possible. A recent study demonstrated that good recoveries can also be obtained with simple protein precipitation with 2-propanol [16]. This method was compared with three other protein precipitation methods and with four extraction methods, including the modified Folch extraction and extraction with MBTE.…”
Section: Sample Preparationmentioning
confidence: 99%